Origin names of gochu, kimchi, and bibimbap - Hye-Jeong Yang; Dai-Ja Jang; Kyung Rhan Chung; Kang-sung Kim; Dae Young Kwon (Journal of Ethnic Foods, 2015)
Background: Despite the long history of Korean foods, the truth and history behind them are either scaled down or distorted due to several scholars who happen to “know” hanja (漢字). A representative case is the distortion of the history of gochu, which inflicts serious distortion on foods that also use the very ingredient. As the distorted history of gochu is pushed forward to be true, the history and the origin name words for gochu, gochujang, and bibimbap are perverted as a result. Hence, food research will proceed in the right direction when such misrepresented origin names are corrected. Methods: This paper aims to correct the existing inaccurate theories by following the principal that the existence of objects come before their written records, analyzing the actual old records of gochu, kimchi, and bibimbap, and integrating them with the development process of Korean verbal and written language. In addition, reasons as to why scholars resorted to such distorted claims will be explained. Results: It is entirely wrong to take hanja names as the origin names for Korean traditional foods simply based on the hanja records of these foods or agricultural products. The hanja records only mean that the Korean people simply borrowed hanja to write the names of the foods they made and enjoyed for a long time. This being said, the claims that the origins names for gochu, kimchi, and bibimbap are gocho (苦椒), chimchae (沈菜), and koldonban (滑董飯) are false. In fact, the correct ones are gochyo (고쵸), dimchae (딤), and bubuimbap (부뷤밥). The reason why scholars kept on arguing that the hanja names are the origin names lies in their attempt to distort the history of gochu, kimchi, and bibimbap in order to rationalize their claims that gochu were introduced during Imjinwareran War—the Japanese Invasion of Korea in 1592. Conclusion: Gochu, kimchi, and bibimbap have thousands of years of history and have been called with pure Korean name words. It was only that they were recorded in the form of hanja during the time written Korean was undervalued where people insisted borrowing Chinese characters to write despite written Korean being available. Thus, gocho (苦椒), chimchae (沈菜), and koldonban (滑董飯) are not the origin names. The pure Korean names used even by the people back then are the actual ones: gochyo (고쵸), dimchae (딤), and bubuimbap (부뷤밥).